THEORETICAL ASPECTS OF HUMAN RESOURCES CAPACITY DEVELOPMENT - Yu. A. Zinnurova; E. M. Shironina (Вестник университета)
Human resources capacity in research is considered through the identification of HR capacity and labor potential by identifying common features or differentiating the concepts of HR capacity and labor potential. In the context of organization management, it is important to take into account direction of managerial decisions. This circumstance has determined the author‘s classification of elements of HR capacity in three  blocks: business orientation (level of knowledge, competence and competency skills, physical development, discipline), power orientation (age and gender, social and professional status, organizational skills and leadership), people orientation (communication skills, emotional culture and emotional abilities, corporate identity). HR capacity development programs based on consideration of these blocks has the focus on ensuring strategic coherence.